ANALISIS PENDAYAGUNAAN SUMBER PEMBIAYAAN PERBANKAN UNTUK PERUMAHAN - Irawan, Towaf Totok (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
The bank is considered not maximal yet to finance housing because it is faced with prudential rules in managing third party funds. In general, banks still face a gap between funding sources and housing finance. But the reality of banking financing sources is still the foundation of housing finance. Without reducing the precautionary aspect, the potential for bank funds can be extracted for housing finance. Therefore, it is necessary to analyze the potential for housing finance by banks. After analysis, the banks studied have the potential to carry out housing finance, even though funding sources are obtained from different funding sources. Keywords: Utilization, financing sources, housing